Active Aging for Individuals with Parkinson’s Disease: Definitions, Literature Review, and Models - Seyed-Mohammad Fereshtehnejad; Johan Lökk (Parkinson's Disease)
Active aging has been emerged to optimize different aspects of health opportunities during the aging process in order to enhance quality of life. Yet, most of the efforts are on normal aging and less attention has been paid for the elderly suffering from a chronic illness such as Parkinson’s disease (PD). The aim of this review was to investigate how the concept of “active aging” fit for the elderly with PD and to propose a new model for them using the recent improvements in caring models and management approaches. For this purpose, biomedical databases have been assessed using relevant keywords to find out appropriate articles. Movement problems of PD affect physical activity, psychiatric symptoms lessen social communication, and cognitive impairment could worsen mental well-being in elderly with PD, all of which could lead to earlier retirement and poorer quality of life compared with healthy elderly. Based on the multisystematic nature of PD, a new “Active Aging Model for Parkinson’s Disease” is proposed consisting of self-care, multidisciplinary and interdisciplinary care, palliative care, patient-centered care, and personalized care. These strategies could potentially help the individuals with PD to have a better management approach for their condition towards the concept of active aging.